Estudo de reações sólido/líquido e sólido/gás em altas temperaturas: o caso das reações do PbSO4EPbO no processo pirometalúrgico de reciclagem de Pb a partir de baterias chumbo-ácido - Santin, Betânia de Oliveira (Universidade Federal de São Carlos, 2012)
This report presents a study on there reactions and transformations occurring at high temperatures with the two main constituents of scrap lead-acid batteries (Pb/H2SO4) oxide and lead sulphate (PbSO4 and PbO). It was conducted through simulations of possible reactions occurring in a pyrometallurgical process for reprocessing these devices discarded where, besides the battery scrap, different percentages of coking coal (C), iron chip and sodium carbonate (Na2CO3). As the literature pointed PbO as a product of many intermediate reactions in the production of secondary or recycled Pb, it was given the same importance to PbSO4, which is the main component of scrap batteries Pb/ H2SO4. For the implementation of this thesis, a mini pilot plant was designed and constructed with good temperature control of this metallurgical process. Using this tool a study of variation of them ass of the compounds treated thermally separated and in mixtures, was performed in a temperature range of 100 oC to 1000 oC. In general, the compounds and thermally treated mixtures were characterized via Absorption Spectroscopy Infrared and Raman Spectroscopy. Spectroscopic data were analysed by comparions with standard spectra of pure substances or, in the case of the mixtures, of these components already treated thermally separated. Contrary to what has been described in the literature, it has been found experimentally that PbO is not reduced by simply reducing the atmosphere generated by adding C in the oven, but by a combination of this with the reducing atmosphere generated by the flame used for heating the Scrap loads with all the other added reagents. Even under the conditions applied in this study, contrary to the hither to described in the literature, Fe chips did not act reducing the PbSO4. However, in the presence of C, the reduction temperature of this sulphate to PbO decreased considerably. When Na2CO3 was added to the mixturePbSO4 + C this decomposition temperature further
Keywords: Metalurgia; Baterias chumbo-ácido; Reciclagem de chumbo; Raman, Espectroscopia de; CIENCIAS EXATAS E DA TERRA::QUIMICA